Do Economic Growth and Urbanization Drive CO2 Emissions? Role of Renewable Energy and Energy Efficiency in Indonesia - Destiartono, Mohamad Egi (International Journal of Energy Economics and Policy, 2025)
This study aims to investigate whether the damaging impact of rapid urbanization and economic growth on the environment is evident in the case of Indonesia while simultaneously looking at the role of renewable energy and energy efficiency. The current study utilizes yearly data (1991–2021) to establish the Augmented Environmental Kuznets Curve (EKC) model. For the method, an Autoregressive Distributed Lag (ARDL)-Bounds testing, Toda-Yamamoto (TY) causality, and Zivot-Andrews (ZA) test are employed. As the result of that cointegration is evidence, urbanization is verified as a driver of environmental degradation since it is positively connected to CO2. Energy intensity is found to have a positive impact on CO2; hence, increasing energy efficiency is pivotal. Renewable energy is confirmed to have a vigorous role in reducing emissions since it is negatively linked to CO2. The association between per capita income and CO2 is found to follow an inverse U-shaped, as suggested by the EKC hypothesis, showing that economic growth can be applied as an instrument for sustainable development. Bidirectional causalities are predominant among the observed variables. Following the findings, fostering energy transition by enhancing clean energy use while simultaneously improving energy efficiency is a crucial scheme to reduce CO2 emissions in Indonesia.